Análisis de dos modelos evaluativos referidos a la química de COU y selectividad (primeros resultados) - López, N.; Llopis, R.; LLorens Molina, J. A.; Salinas, B.; Soler, J. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
This article is about the content and analysis of examinations and assessment in a specific field: the teaching of Chemistry. We compare the results obtained by students in different internal test during and the end of an academic year with those obtained by the same students in art external test set by the entrance examination board at the University of Valencia.